PEMANFAATAN VIRTUALBOX DALAM KONEKSI DENGAN WINBOX DI SMK NEGERI 1 PORTIBI - Zainy, Ahmad; Fauzi, Rahmad; Nurdiansyah, Aldi (Institut Pendidikan Tapanuli Selatan, 2025)
Practical observations on the use of Virtualbox in connection with Winbox were carried out at SMK Negeri 1 Portibi which is located at Napahalas village, Napa Halas, Kec. Portibi, Kab. North Padang Lawas Province. North Sumatra. This observation aims to provide additional knowledge to students about using Winbox with VirtualBox as well as carrying out practices in using Winbox with VirtualBox. This observation activity was shown to Class XI TKJ Students at SMK Negeri 1 Portibi. The number of students who have been reviewed by the implementation team is 17 students. The observation data reviewed is students' responses to using Winbox with Virtual Box. Virtual Box is a technique for hiding the physical characteristics of computing resources from the resource's interactions with other systems, applications, or users. This is a single resource server, operating systems including. This virtualbox software is only needed to try and learn to install the operating system. Therefore, you can easily install Linux on Windows just by using the VirtualBox application.